The Difference between Computed Tomography and Magnetic Resonance Imaging Measurements of Tibial Tubercle–Trochlear Groove Distance for Patients with or without Patellofemoral Instability: A Systematic Review and Meta-analysis - Tan, Si Heng Sharon; Lim, Beatrice Ying; Chng, Kiat Soon Jason; Doshi, Chintan; Wong, Francis K.L.; Lim, Andrew Kean Seng; Hui, James Hoipo (The Journal of Knee Surgery, 2020)
The tibial tubercle–trochlear groove (TT–TG) distance was originally described for computed tomography (CT) but has recently been used on magnetic resonance imaging (MRI) without sufficient evidence demonstrating its validity on MRI. The current review aims to evaluate (1) whether there is a difference in the TT–TG distances measured using CT and MRI, (2) whether both the TT–TG distances measured using CT and MRI could be used to differentiate between patients with or without patellofemoral instability, and (3) whether the same threshold of 15 to 20 mm can be applied for both TT–TG distances measured using CT and MRI. The review was conducted using the preferred reporting items for systematic reviews and meta-analyses (PRSIMA) guidelines. All studies that compared TT–TG distances either (1) between CT and MRI or (2) between patients with and without patellofemoral instability were included. A total of 23 publications were included in the review. These included a total of 3,040 patients. All publications reported the TT–TG distance to be greater in patients with patellofemoral instability as compared to those without patellofemoral instability. This difference was noted for both TT–TG distances measured on CT and on MRI. All publications also reported the TT–TG distance measured on CT to be greater than that measured on MRI (mean difference [MD] = 1.79 mm; 95% confidence interval [CI]: 0.91–2.68). Pooling of the studies revealed that the mean TT–TG distance for the control group was 12.85 mm (95% CI: 11.71–14.01) while the mean TT–TG distance for patients with patellofemoral instability was 18.33 mm (95% CI: 17.04–19.62) when measured on CT. When measured on MRI, the mean TT–TG distance for the control group was 9.83 mm (95% CI: 9.11–10.54), while the mean TT–TG distance for patients with patellofemoral instability was 15.33 mm (95% CI: 14.24–16.42). Both the TTTG distances measured on CT and MRI could be used to differentiate between patients with and without patellofemoral instability. Patients with patellofemoral instability had significantly greater TT–TG distances than those without. However, the TT–TG distances measured on CT were significantly greater than that measured on MRI. Different cut-off values should, therefore, be used for TT–TG distances measured on CT and on MRI in the determination of normal versus abnormal values. Pooling of all the patients included in the review then suggest for 15.5 ± 1.5 mm to be used as the cut off for TT–TG distance measured on CT, and for 12.5 ± 2 mm to be used as the cut-off for TT–TG distance measured on MRI. The Level of evidence for this study is IV.
Keywords: patellar instability; patellofemoral instability; tibial tubercle–trochlear groove; TT–TG; computed tomography; magnetic resonance imaging